Dental care before cardiac valve surgery: Is it important to prevent infective endocarditis?. (September 2016) - de Souza, Alessandra Figueiredo; Rocha, Amanda Leal; Castro, Wagner Henriques; Ferreira, Fernanda Morais; Gelape, Claudio Léo; Travassos, Denise Vieira; da Silva, Tarcília Aparecida
Abstract: Background: Infective endocarditis (IE) is a serious disease that affects the surface of the endocardium. The spread of microorganisms from the oral cavity has been associated with the occurrence of IE. Objective: To analyze whether dental treatment before cardiac valve surgery (CVS) influenced the occurrence of IE. Methods: We performed a retrospective analysis of the medical and dental histories of patients undergoing CVS from 2004 to 2014. The sample consisted of 481 patients who underwent CVS divided into two groups: patients submitted to dental treatment prior to CVS (n = 110) and patients undergoing CVS without dental treatment (n = 371). Results: Of the total sample, 38 patients (8%) were diagnosed with IE. No significant difference was detected (p = 0.496) in comparing the occurrence of IE in the group with dental preparation (6.4%) and without dental preparation (8.4%). The logistic regression model confirmed that dental treatment did not change the IE risk (p = 0.504) and indicated that age (p < 0.003) and gender (p = 0.013) were significant risk factors for IE. There was a high demand for dental procedures in the group receiving dental preparation, with no significant differences between the patients with or without IE. Hemoculture indicated qualitative differences in comparing patients with and without dental treatment, especially in the frequency of Staphylococcus and Streptococcus . Conclusions: The results did not allow for the determination of the impact of dental treatment before CVS on IE outcomes. However, it was not possible to exclude the potential beneficial effects of dental treatment in the prevention of IE.